PENINGKATAN KEMAMPUAN MEMBACA CEPAT MENGGUNAKAN METODE SQ3R DI KELAS V SDN 07 PONTIANAK UTARA - Nurmiati, Nurmiati; Asmayani, Asmayani; Asmayani, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This study aims to provide descriptions of the use of Survey method, Question, Read, Recite, SQ3R Review so as to improve the ability to read quickly. The benefits of this research are to improve the quality of Indonesian language learning as well as to develop the potential of students' ability as a whole. The research used descriptive method with class action research type. The result of the research shows that in preparing phase, reading and post reading, it can be seen that the percentage that happened at first cycle implementation of second and second meeting is obtained on average 64,30. Completed students are 12 people (60%) while the unfinished there are 8 people (40%). Implementation of cycle II first and second meeting obtained the average value of 84.70 students who complete is 16 people (80%) while the unfinished there are 4 people (20%). From the results of percentage in each cycle can be concluded that there is a significant increase in each cycle. Thus the research using SQ3R method on learning Indonesian language can improve the ability to read fast class V students of Primary School Negeri 07 North Pontianak. Keywords: Fast reading ability, SQ3R Method